THE INFLUENCE OF MEANINGFUL WORK, WORK-LIFE BALANCE, AND AN INCLUSIVE WORK ENVIRONMENT ON THE PREFERENCES OF GENERATION Z STUDENTS AT MALIKUSSALEH UNIVERSITY IN CHOOSING A JOB - Mutia Triani; Likdanawati; Marbawi; Khairawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Meaningful work, work-life balance, and an inclusive work environment are factors that Generation Z considers when choosing a job. As part of Generation Z, students have different perspectives when determining their career preferences. This study aims to investigate the influence of meaningful work, work-life balance, and an inclusive work environment on the career preferences of students at Malikussaleh University when choosing a job. The study employs a quantitative approach using a survey method. Primary data were collected using a research instrument in the form of a questionnaire, with a total of 100 respondents from Malikussaleh University. The data analysis techniques used were multiple linear regression and t-test (partial). The results of the study indicate that meaningful work has a positive and significant influence on students' preferences with a significance value of 0.002 (< 0.05). Work-life balance has a positive but insignificant effect with a significance value of 0.674 (> 0.05). An inclusive work environment has a positive and significant effect on students' preferences in choosing a job with a significance value of 0.001 (< 0.05). Simultaneously, the three variables significantly influence students' preferences, with a significance level of 0.000 and an Adjusted R² value of 0.267. This means that 26.7% of the variation in students' preferences in choosing a job can be explained by these three variables, while the rest is influenced by other factors not examined in this study.